An Interdisciplinary Framework of Character Building in a Digital-Based Boarding School: Scaffolding Honesly and Discipline - Ramadhan, Affan; Achadi, Muh. Wasith (Indonesian Journal of Action Research, 2026)
Purpose – This research aimed to investigate the reinforcement of student character education amidst massive digital disruption, hypothesizing that an interdisciplinary model combining technological regulation, institutional rituals, and peer-led interventions significantly enhances moral resilience. Design/methods– The study employed a qualitative descriptive design conducted at a centralized boarding school in Indonesia, chosen for its integrated digital governance. Data collection procedures involved participant observation and in-depth interviews with students and educators, focusing on variables such as digital transparency, peer conformity, and behavioral habituation. Findings – Results indicated that implementing school-based applications for attendance and permits served as effective moral scaffolding, fostering honesty and accountability through transparent data tracking. Furthermore, periodic restrictions on gadget access were found to mitigate dopaminergic-driven distractions, allowing students to practice tangible time discipline and self-regulation. The findings also revealed that peer modeling and cooperative learning successfully transformed "herd mentality" into positive social imitation, significantly increasing student engagement in religious and academic rituals. These results imply that educational policies must transition from passive, conventional instruction to active, technological adaptations that align with adolescent neurobiological development. Future studies should consider longitudinal analysis to evaluate the long-term sustainability of these digital-moral habits. This paper includes 50 references and 12 tables, including interview protocols and technological monitoring instruments